Comparative gonad transcriptome analysis in cobia (Rachycentron canadum) - Shen, Xueyan; Yáñez, José M.; Bastos Gomes, Giana; Poon, Zhi Weng Josiah; Foster, Derick; Alarcon, Jorge F.; Domingos, Jose A. (Frontiers in Genetics, 2023)
Background: Cobia (Rachycentron canadum) is a species of fish with high commercial potential particularly due to fast growth rates. The evidence of sexual size dimorphism favoring females indicate potential benefits in having a monosex culture. However, the involvement of genetic factors responsible for sexual development and gonadal maintenance that produces phenotypic sex in cobia is largely unknown. Methods: In the present study, we performed transcriptome sequencing of cobia to identify sex-biased significantly differentially expressed genes (DEGs) in testes and ovaries. The reliability of the gonad transcriptome data was validated by qPCR analysis of eight selected significantly differential expressed sex-related candidate genes. Results: This comparative gonad transcriptomic analysis revealed that 7,120 and 4,628 DEGs are up-regulated in testes or ovaries, respectively. Further functional annotation analyses identified 76 important candidate genes involved in sex determination cascades or sex differentiation, including 42 known testis-biased DEGs (dmrt1, amh and sox9 etc.), and 34 known ovary-biased DEGs (foxl2, sox3 and cyp19a etc.). Moreover, eleven significantly enriched pathways functionally related to sex determination and sex differentiation were identified, including Wnt signaling pathway, oocyte meiosis, the TGF-beta signaling pathway and MAPK signaling pathway. Conclusion: This work represents the first comparative gonad transcriptome study in cobia. The putative sex-associated DEGs and pathways provide an important molecular basis for further investigation of cobia’s sex determination, gonadal development as well as potential control breeding of monosex female populations for a possible aquaculture setting.